THE INFLUENCE OF GOVERNMENT EXPENDITURE AND ECONOMIC GROWTH ON EMPLOYMENT REGENCY / CITY IN PROVINCE WEST KALIMANTAN YEAR 2009-2013 - B01111035, Kartika Jannah (Jurnal Curvanomic, 2016)
The title of this research is "The Influence of Government Expenditure and EconomicGrowth on Employment Regency / City in Province West Kalimantan Year 2009-2013". Thisstudy aims to determine the effect of government expenditure and economic growth onemployment. This study used quantitative descriptive method using panel data regression model,as well as R Square test, F test and t test to test the hypothesis whether government expenditureand economic growth effect on employmentThese results indicate that of government expenditure the positive effect amounted to0.013112 and significant, while of economic growth the positive effect amounted to 0.041885and significant employment opportunities in the regency / city in Province West Kalimantan2009-2013. The coefficient of determination (R2) amounted to 0.892243, which means themagnitude of the impact that government spending and economic growth Regency / City inProvince West Kalimantan Year 2009 to 2013 amounted to 89%, while the remaining 11% areinfluenced by other factors.Keywords :employment Opportunity, government Expenditure, economic growth